A educação permanente em saúde e sua relação com os processos de trabalho nos centros de especialidades odontológicas - Martins, Yuri Victor de Medeiros (2023)
The National Policy for Permanent Education in Health, instituted in Brazil in 2004, emerged as a theoretical and methodological basis for instructions for the training and development of health workers. It understands the qualification of workers as being based primarily on the health needs of users and local reality. The structuring of work processes must be based on the problematization of practice. Thus, Permanent Health Education responds to the social character of the educational action carried out at work allied to multidisciplinary teamwork and seeks to achieve a primordial technical training. The general objective of this thesis was to find out how Permanent Health Education actions are inserted into the work processes at Dental Specialty Centers. Each specific objective was aimed at producing a scientific article. They are: a) to analyze the relationship between Permanent Health Education actions and the work process and the impact on comprehensiveness in the routines of Dental Specialty Centers; b) to analyze Permanent Health Education actions, their association with the work process in Dental Specialty Centers and their relationship with primary care; c) to verify the impact that Permanent Health Education actions can have on user satisfaction and d) to verify the importance of self-assessment for the production and certification of Dental Specialty Centers. This thesis was divided into four articles. They are all exploratory cross-sectional studies based on secondary data from the 2nd Cycle of the National Program for Improving Access and Quality in Dental Specialty Centers. Logistic regression models were fitted to all four articles, assuming a statistical significance level of 5%. In article 1, the results showed that where there is matrix support, there are more chances (OR 26; 95% CI, 9.36 - 71.87) of continuing education actions taking place, as well as the presence of a manager with training in Collective Health (OR 1.72; 95% CI, 1.23 - 2.40), incentive, bonus or financial award given to professionals for performance (OR 1.58; 95% CI, 1.13 - 2.22), periodically organized planning and evaluations (OR 2.94; 95% CI, 1.46 - 5.90) and the practice of self-assessment (OR 3.05; 95% CI, 2.04 - 4.55) increase the chance of these educational actions taking place. In article 2, the analysis showed that in centers where Permanent Health Education is carried out in an integrated manner with primary care professionals, there are more chances (OR 3; 95% CI, 1.14 - 9.25) of jointly constructing therapeutic projects and more chances (OR 4; 95% CI, 2.90 - 5.75) of discussions and constructing clinical protocols. The most robust statistical value of article 3 indicates that the Permanent Health Education actions originating from the municipal organization increase the chances of users attributing positive values to the service. Furthermore, these values have an 88% chance of increasing when the actions involve primary care and medium-complexity professionals. The analysis of article 4 showed that CEOs where the work process included self-assessment were more likely (OR 2; 95% CI, 1.25 - 3.44) to achieve better production rates and 40% more likely to achieve better certification scores. These studies showed the importance of management commitment and action to carry out Permanent Health Education practices and the relationship between Permanent Health Education actions and the strengthening of comprehensive care in medium-complexity dental care practiced in Dental Specialty Centers.